Emerging Trends in Fluorescence Bioimaging of Divalent Metal Cations Using Small‐Molecule Indicators - Liu, Mingqiao; Zhang, Junwei; Chen, Zhixing (Chemistry : a European journal, 2022)
Visualization of cation dynamics inside a living system represent a major breakthrough at the crossroad of chemistry and cellular physiology. Since the inception of BAPTA‐based cellular calcium indicators in the 1980s, generations of chemical and genetically encoded ion indicators spanning the visible spectrum have been developed. In this article, we bring up three emerging concepts in this field: 1. red‐shifting cation indicators towards far‐red and near‐infrared (NIR) channels; 2. directing the indicators to various subcellular localizations; 3. lowering the phototoxicity of indicators for long term recording. These initiatives collectively echo the advocate of 4D cellular physiology, where biological processes within living systems can be panoramically unveiled under 3D, long‐term, and multi‐channel imaging with unprecedented spatial and temporal resolution. This outlook poses exciting challenges and opportunities for chemists to upgrade the toolkit of fluorescent indicators as key enablers for a new era of imageomics. Visualization of cation dynamics inside living systems represent a major breakthrough at the crossroad of chemistry and cellular physiology. In this article, we bring up three emerging concepts in this field: 1) Red‐shifting cation indicators towards far‐red and NIR channels; 2) directing the sensors to various subcellular localizations; 3) lowering the phototoxicity of sensors for long term recording. These initiatives collectively echo the advocate of 4D physiology, in which biological processes within living systems can be panoramically unveiled under 3D, long‐term, and multi‐channel imaging with unprecedented spatial and temporal resolutions.